2022
DOI: 10.15585/mmwr.ss7106a1
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Violent Deaths — National Violent Death Reporting System, 42 States, the District of Columbia, and Puerto Rico, 2019

Abstract: Problem/Condition In 2019, approximately 67,000 persons died of violence-related injuries in the United States. This report summarizes data from CDC’s National Violent Death Reporting System (NVDRS) on violent deaths that occurred in 42 states, the District of Columbia, and Puerto Rico in 2019. Results are reported by sex, age group, race and ethnicity, method of injury, type of location where the injury occurred, circumstances of injury, and other selected characteristics. Period C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 41 publications
3
32
0
Order By: Relevance
“…Similarly, more alcohol and other substance use circumstances, including those of an acute and more chronic nature, were observed in this study, as were criminal problems, although the nature of these problems was unknown. According to previous NVDRS reports, approximately one half of persons who die by suicide do not have a known mental health condition ( 4 ). This study found that only 41.5% of AI/AN suicide decedents had a known mental health condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, more alcohol and other substance use circumstances, including those of an acute and more chronic nature, were observed in this study, as were criminal problems, although the nature of these problems was unknown. According to previous NVDRS reports, approximately one half of persons who die by suicide do not have a known mental health condition ( 4 ). This study found that only 41.5% of AI/AN suicide decedents had a known mental health condition.…”
Section: Discussionmentioning
confidence: 99%
“…NVDRS is a state-based surveillance system that collects information from death certificates, coroner or medical examiner reports, and law enforcement reports on the characteristics and circumstances of violent deaths, including suicides ( 4 ). Data in this report are from the District of Columbia, Puerto Rico, and 49 U.S. states participating in NVDRS during 2015–2020 * ; some jurisdictions did not participate for the entire period because they were not yet funded or because they did not achieve data completion thresholds (Supplementary Table, https://stacks.cdc.gov/view/cdc/121071 ) ( 4 ). Analyses were limited to decedents aged ≥10 years, because determining suicide intent in young children can be difficult ( 5 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Child physical abuse is experienced by approximately one-quarter of children at some point in their lives and by as many as 1 in 5 girls are sexually abused during childhood . Intimate partner violence has been experienced by about one-third of both women and men, and half of homicides among women are related to intimate partner violence . Elder abuse, in the form of physical, sexual, and psychological abuse, is experienced by approximately 10% to 15% of people aged 60 years or older living in the US, with an estimated 95% of incidents going unreported.…”
mentioning
confidence: 99%